Dermatophytoses Caused by Trichophyton indotineae: The First Case Reports in Malaysia and the Global Epidemiology (2018–2025) - Yi Xian Er; Kin Fon Leong; Henry Boon Bee Foong; Anis Amirah Abdul Halim; Jing Shun Kok; Nan Jiun Yap; Yuong Chin Tan; Sun Tee Tay; Yvonne Ai-Lian Lim (Journal of Fungi)
Trichophyton indotineae is emerging globally from its origin in India, presenting with a terbinafine resistance and causing significant clinical burden. We report herein the first four confirmed cases of T. indotineae dermatophytoses in Malaysia, which were diagnosed based on the microscopic examination of skin scrapings using potassium hydroxide (KOH) wet mount, followed by confirmation via culture and Internal Transcribed Spacer (ITS1) sequencing. In contrast to conventional Trichophyton infections, T. indotineae dermatophytoses demonstrate extensive cutaneous involvement and marked inflammation with erythematous lesions. All cases exhibited a chronic course lasting more than three months, with evidence of person-to-person transmission. Although one patient reported a travel to Singapore, three had no recent travel history, suggesting possible local transmission. The isolates produced characteristic white, cottony colonies with radial mycelial growth on Mycosel agar after incubation at 30 °C for four days. Three patients responded well to oral itraconazole (200 mg daily), with reduced inflammation and erythematous lesions observed two weeks after treatment initiation. The occurrence of T. indotineae particularly among patients without a travel history, suggests a potential endemic establishment. This fungal pathogen warrants consideration in cases of extensive or recalcitrant dermatophytoses. Further investigations into the diagnostic methods, antifungal susceptibility profiles, and epidemiological risk factors of Malaysian strains are warranted to enhance clinical management and inform public health interventions.